New synthesis of 6″‐[18F]fluoromaltotriose for positron emission tomography imaging of bacterial infection. (21st July 2020) - Gabr, Moustafa T.; Haywood, Tom; Gowrishankar, Gayatri; Srinivasan, Ananth; Gambhir, Sanjiv S.
Abstract : 6″‐[ 18 F]fluoromaltotriose is a positron emission tomography tracer that can differentiate between bacterial infection and inflammation in vivo. Bacteria‐specific uptake of 6″‐[ 18 F]fluoromaltotriose is attributed to the targeting of maltodextrin transporter in bacteria that is absent in mammalian cells. Herein, we report a new synthesis of 6″‐[ 18 F]fluoromaltotriose as a key step for its clinical translation. In comparison with the previously reported synthesis, the new synthesis features unambiguous assignment of the fluorine‐18 position on the maltotriose unit. The new method utilizes direct fluorination of 2″, 3″, 4″‐tri‐O‐acetyl‐6″‐O‐trifyl‐ α ‐D ‐glucopyranosyl‐(1‐4)‐O‐2′, 3′, 6′‐tri‐O‐acetyl‐ α ‐D‐glucopyranosyl‐(1‐4)‐1, 2, 3, 6‐tetra‐O‐acetyl‐D‐glucopyranose followed by basic hydrolysis. Radiolabeling of the new maltotriose triflate precursor proceeds using a single HPLC purification step, which results in shorter reaction time in comparison with the previously reported synthesis. Successful synthesis of 6″‐[ 18 F]fluoromaltotriose has been achieved in 3.5 ± 0.3% radiochemical yield (decay corrected, n = 7) and radiochemical purity above 95%. The efficient radiosynthesis of 6″‐[ 18 F]fluoromaltotriose would be critical in advancing this positron emission tomography tracer into clinical trials for imaging bacterial infections. Abstract : We report a new radiosynthesis of 6″‐[ 18 F]fluoromaltotriose for imaging bacterial infections.